Antioxidant status and oxidative stress at rest and in response to acute exercise in judokas and sedentary men - Abed, K. E.; Rebai, H.; Bloomer, R. J.; Trabelsi, K.; Masmoudi, L.; Zbidi, A.; Sahnoun, Z.; Hakim, A.; Tabka, Z. (The Journal of Strength and Conditioning Research, 2011)
It is well recognized that acute strenuous exercise is accompanied by an increase in free-radical production and subsequent oxidative stress, in addition to changes in blood antioxidant status. Chronic exercise provides protection against exercise-induced oxidative stress by upregulating endogenous antioxidant defense systems. Little is known regarding the protective effect afforded by judo exercise. Therefore, we determined antioxidant and oxidative stress biomarkers at rest and in response to acute exercise in 10 competitive judokas and 10 sedentary subjects after mixed exercise (anaerobic followed by aerobic). The subjects performed a Wingate test, followed by 30 minutes of aerobic exercise performed at 60% of maximal aerobic power. Blood samples were taken, by an intravenous catheter, at rest (R), immediately after the physical exercise (P0), and at 5 (P5), 10 (P10), and 20 (P20) minutes postexercise. The measured parameters included the activity of the antioxidant enzymes superoxide dismutase, glutathione peroxidase, and glutathione reductase, in addition to alpha-tocopherol, and total antioxidant status. Malondialdehyde was measured as a representation of lipid peroxidation. At rest, the judokas had higher values for all antioxidant and oxidative stress markers as compared to the sedentary subjects (p < 0.05). Plasma concentrations of all parameters except for alpha-tocopherol increased significantly above resting values for both the judokas and sedentary subjects (p < 0.05) and remained elevated at 20 minutes postexercise. A significant postexercise decrease was observed for alpha-tocopherol (p < 0.05) at P20 for judokas and at P5 for sedentary subjects. These data indicate that competitive judo athletes have higher endogenous antioxidant protection compared to sedentary subjects. However, both groups of subjects experience an increase in exercise-induced oxidative stress that is not different.